2020
DOI: 10.1007/s13304-020-00878-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of the comprehensive complication index for the prediction of survival after liver transplantation

Abstract: In the last years, several scoring systems based on pre- and post-transplant parameters have been developed to predict early post-LT graft function. However, some of them showed poor diagnostic abilities. This study aims to evaluate the role of the comprehensive complication index (CCI) as a useful scoring system for accurately predicting 90-day and 1-year graft loss after liver transplantation. A training set (n = 1262) and a validation set (n = 520) were obtained. The study was registered at https://www.Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Previous studies have reported that CCI had prognostic value for graft survival over a relatively short term (within 1 year) 17,18 . One study found that a cutoff value of 47.3 was quite useful because the 1-year liver graft survival rate dropped significantly above this threshold 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that CCI had prognostic value for graft survival over a relatively short term (within 1 year) 17,18 . One study found that a cutoff value of 47.3 was quite useful because the 1-year liver graft survival rate dropped significantly above this threshold 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Dindo-Clavien grade I corresponds to 8.7, grade II to 20.9, grade IIIa to 26.2, grade IIIb to 33.7, grade IVa to 42.4, grade IVb to 46.2, and grade V to 100. In the liver transplantation setting, CCI has shown a good prediction ability for 90-day and 1-year graft loss risk (19). The CCI ranges from 0 (i.e., absence of post-operative complications) to 100 (i.e., death) (12,18).…”
Section: Definitionsmentioning
confidence: 99%
“…In patients exceeding the CCI ninth percentile, 1-y graft survival rates were 0.7% and 23.1% in training and validation cohorts, respectively. 14 Other RCTs suggested a 1-y cumulative CD complication ≥3 and CCI as secondary endpoints 64 (Figure 4).…”
Section: The Value Of Current Endpoints In Liver Transplantation Studiesmentioning
confidence: 99%
“…[10][11][12] As a result of the limited practicability of conventional endpoints attributed to fewer such events, short-term outcomes, and noninferiority have become more common. 11 With patient and graft survival rates exceeding 80% at 1 y, complications as assessed with the Clavien-Dindo (CD) 13 classification (2004) and a few years later (2013) the Comprehensive Complication Index (CCI) 14 were adopted as secondary or surrogate endpoints (SEs) in LT. The expansion of LT for oncological diseases, particularly for HCC as the fifth most common malignancy and the third most common cause of cancer-related mortality, 15 is defined by recurrence risk assessment as, for example, defined by the Milan criteria in 1996.…”
Section: A Brief History Of Endpoints In Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation